2019
DOI: 10.1017/jsl.2019.71
|View full text |Cite
|
Sign up to set email alerts
|

Existentially Closed Brouwerian Semilattices

Abstract: The variety of Brouwerian semilattices is amalgamable and locally finite, hence by well-known results [Whe76], it has a model completion (whose models are the existentially closed structures). In this paper, we supply for such a model completion a finite and rather simple axiomatization.2010 Mathematics subject classification. Primary 03G25; Secondary 03C10, 06D20.A co-Brouwerian semilattice, CBS for short, is a structure obtained by reversing the order of a Brouwerian semilattice. We will work with CBSes inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…First notice that, as a consequence of (10), if the cardinality of X B0 and of X C is the same, then f is an isomorphism. This is seen as follows: we already observed that condition (10) implies surjectivity and in case of the same finite cardinality surjectivity implies injectivity. Preservation and reflection of the relation follow by stability and (10) again.…”
Section: Admissibility and Modelmentioning
confidence: 76%
See 4 more Smart Citations
“…First notice that, as a consequence of (10), if the cardinality of X B0 and of X C is the same, then f is an isomorphism. This is seen as follows: we already observed that condition (10) implies surjectivity and in case of the same finite cardinality surjectivity implies injectivity. Preservation and reflection of the relation follow by stability and (10) again.…”
Section: Admissibility and Modelmentioning
confidence: 76%
“…Proof. We need to show that f satisfies condition (10) above iff f ⋆ is an embedding between contact algebras, i.e. iff it satisfies the condition…”
Section: Admissibility and Modelmentioning
confidence: 99%
See 3 more Smart Citations